2017
DOI: 10.1051/0004-6361/201629731
|View full text |Cite
|
Sign up to set email alerts
|

XMM-Newtonand INTEGRAL view of the hard state of EXO 1745−248 during its 2015 outburst

Abstract: Context. Transient low-mass X-ray binaries (LMXBs) often show outbursts lasting typically a few-weeks and characterized by a high X-ray luminosity (L x ≈ 10 36 − 10 38 erg s −1 ), while for most of the time they are found in X-ray quiescence (L X ≈ 10 31 − 10 33 erg s −1 ). EXO 1745-248 is one of them. Aims. The broad-band coverage, and the sensitivity of instrumet on board of XMM-Newton and INTEGRAL, offers the opportunity to characterize the hard X-ray spectrum during EXO 1745-248 outburst. Methods. In this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 76 publications
2
18
0
Order By: Relevance
“…Matranga et al 2017), although we do find a small decrease in strength at the lowest and highest frequencies. The decrease at high frequencies was not explicitly mentioned by Matranga et al (2017), although it can be seen from their Figure 6 as well.…”
Section: Exo 1745-248mentioning
confidence: 89%
See 3 more Smart Citations
“…Matranga et al 2017), although we do find a small decrease in strength at the lowest and highest frequencies. The decrease at high frequencies was not explicitly mentioned by Matranga et al (2017), although it can be seen from their Figure 6 as well.…”
Section: Exo 1745-248mentioning
confidence: 89%
“…Similarly to Matranga et al (2017) we found that the PDS of EXO 1745-248 (green curve in left panel of Figure 4) is relatively flat over the full frequency range (in the νPν representation, which is different than what was used by 9 When this PDS of 1RXS J180408.9-342058 is fitted with a broken power-law model plus a Lorentzian, the frequencies of those components are 0.72 +0.03 −0.01 Hz and 4.1±0.1 Hz, respectively. These values are fully consistent with the relation found by Wijnands & van der Klis (1999a) for these components.…”
Section: Exo 1745-248mentioning
confidence: 99%
See 2 more Smart Citations
“…Typical values of the reflection amplitude Ω/2π for NS-LMXB atoll sources are within 0.2-0.3 (Matranga et al 2017b;Di Salvo et al 2015;Egron et al 2013;D'Aì et al 2010). However, smaller reflection fractions are also observed for other systems, such as Ser X-1 (Matranga et al 2017a;Cackett et al 2010) and 4U 1820-30 (Cackett et al 2010) and for AMSP SAX J1748.9-2021 .…”
Section: Discussionmentioning
confidence: 87%